Reflections on Citizenship: Thinking About Power as Interaction - Hill, Leslie (Maine Policy Review, 1992)
The steady decline of participation in many areas of public life suggests that we may be overlooking power as not only a source of the problem, but also as a critical part of the solution. Leslie Hill argues that to revive concepts of citizenship and democratic participation enshrined in the language of the nation's founding, we ought to rethink conventional ideas about power as control and domination and, in the alternative, view power as interaction. She also suggests that we need to adopt new approaches to civic education that include this concept of power as interactive politics. Underlying this argument, she asserts, is a fundamental tenet of democratic governance: that all parties in a democracy, not just those with superior wealth, status, or expertise, ought to be involved in initiating, responding to, and determining what the common good is and the most appropriate ways to achieve it.
Keywords: politics; civics; civic education